1991
DOI: 10.1099/00221287-137-1-197
|View full text |Cite
|
Sign up to set email alerts
|

Polar lipids and fatty acids of Pseudomonas caryophylli, Pseudomonas gladioli and Pseudomonas pickettii

Abstract: The polar lipids and their fatty acid components in Pseudomonas cmyophyffi, Pseudomonas g f d o f i and Pseudomonas pickeftii have been identified. In addition to diphosphatidylglycerol and phosphatidylglycerol (a trace only for P. picketfir?, all three species contained two forms of phosphatidylethanolamine differing in the presence or absence of a-hydroxy fatty acids. This seems to be a distinctive feature of species in Pseudomonas RNA homology group 11. Also, P. caryophyffi and P. g f d o f i (but not P. pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…However, the phosphorus content of the lipids was relatively constant and indi- Galbraith & Wilkinson, 1991), broad signals on a noisy background were obtained by the NMR method, so that separate PE peaks were not observed and there was partial overlap of those for DPG and PG. Chromatographic resolution on TLC was also incomplete, so the data obtained by both methods (Table 2) are only given for lipid pairs.…”
Section: Effects Of Growth Temperature On Carbon-limited Cu Itu Resmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the phosphorus content of the lipids was relatively constant and indi- Galbraith & Wilkinson, 1991), broad signals on a noisy background were obtained by the NMR method, so that separate PE peaks were not observed and there was partial overlap of those for DPG and PG. Chromatographic resolution on TLC was also incomplete, so the data obtained by both methods (Table 2) are only given for lipid pairs.…”
Section: Effects Of Growth Temperature On Carbon-limited Cu Itu Resmentioning
confidence: 99%
“…(Galbraith & Wilkinson, 1991;Yabuuchi et al, 1992;Phung et al, 199Sa), whereas certain species recently excised from Burkholderia and Alcaligenes to form the new genus Ralstonia lack both forms of OL (Galbraith & Wilkinson, 1991 ;Yabuuchi et al, 1995). Phenotypic variation of lipid composition in bacteria, including the stimulation of OL production by growth under phosphorus-limiting conditions for at least some Gramnegative species, is a well-known phenomenon (Wilkinson, 1988).…”
Section: H2n( Ch)chcohmentioning
confidence: 99%
See 2 more Smart Citations
“…These bacteria have the same major cellular fatty acid and ubiquinone system components. Galbraith and Wilkinson (14) reported that the nonhydroxy fatty acids of B. caryophylli and B. gladioli consisted of large amounts of n-C16:", n-C18:1, and cyclopropane C,7:o acids and that B. pickettii contained large amounts of n-Clh:O, n-c16:1, n-C18:,, and cyclopropane CI7:" acids. The differences in our results may have been due to the culture age of the cells used, because a decrease in the amount of h?-c16:1 acid and an increase in the amount of cyclopropane C17:o acid with age have been reported previously (48).…”
Section: + + + --+ + -+ + -+ + --+ + -mentioning
confidence: 99%